An Assessment of Counter Insurgency Strategy Against TTP in Tribal Belt (Journal of Social Sciences Review, 2025)
Pakistan’s tribal belt is facing a renewed wave of insurgency with changes in tactics and approaches from TTP. The overall strategic and security environment in the tribal belt is becoming a no-go area again. The challenges are complex. Ranging from past security vacuums to the structural flaws in governance and denial of winning public trust in pre- and post-insurgency scenarios. The resurgence of TTP is a complex phenomenon as a result of complex variables, both internal and external. The leadership of Noor Wali Mehsud played an important role in re-organizing and restructuring TTP in the tribal belt and KP. This issue and counterinsurgency strategy were badly ignored in the tribal belt. The consequences are now in front of state and security forces in Pakistan. Therefore, this paper aims to critically analyze Pakistan's counter-insurgency strategies in the post-military actions in the tribal belt and will look at major policy errors and loopholes in this regard.
Keywords: Counter-Insurgency; Flawed Approach; Governance; Resurgence; Post-Military Operations; Local Grievances; Security Failure